The academic impact of the triological society theses—Mosher and fowler awards: Citations, impact factor, and h‐index. (6th August 2013) - Badran, Karam W.; Lahham, Sari; Mahboubi, Hossein; Crumley, Roger L.; Wong, Brian J.F.
Abstract : Objectives/Hypothesis: The Triological Society requires thesis submission for full membership. Accepted theses (AT) may be recognized with designations of: Mosher Awards (MA), Fowler Awards (FA), Honorable Mention for Basic Science (HMBS), and Honorable Mention for Clinical Science (HMCS). We sought to determine and compare the scholarly impact of Triological Society theses, their authors, and whether differences exist between AT and those that receive special recognition. Study Design: Retrospective analysis of awards and theses compiled by The Triological Society home office from 1998 to 2011. Methods: Thomson Reuters' Integrated Search Interface (ISI) Web of Knowledge and Google Scholar and were used to determine citations and the author's h‐index. Trend and statistical analysis was performed. Results: Of the 307 Triological Society theses examined, 275 were published and had record of citation. H‐indices and number of citations were found to be nonparametric; thus, median and quartile (1 st −3 rd quartiles) values were found to be the following: AT 11 (4–26), MA 18 (9–25), FA 6 (1–28), HMBS 11 (4–26), and HMCS 16 (1–28) for number of citations per published thesis. H‐indices of authors with accepted theses were AT 15 (10–19), MA 16 (15–23), FA 18 (10–23), HMBS 16 (11–19), and HMCS 15 (11–21). When comparing all groupings of theses and award winners with bibliometric indices, no statistical significance was found ( P >0.5). Conclusions: The Triological Society cultivates a competitive pool of applicants as membership is highly regarded. Negligible difference in citations and author h‐index were observed between AT, MA, and FA theses indicated that the level of excellence is uniform, and thesis submission remains influential and prestigious. Level of Evidence: N/A. Laryngoscope, 123:2654–2657, 2013